Association between dietary patterns and hypertension among older adults at the Medan Johor Community Health Center - Waruwu, Inel Hartanti; Ginting, Rapael; Suyono, Tan; Kurniawan, Evan; Sitanggang, Holan Dianju Melva Meinaria; Bestari, Welas; Deseva, Frisca Gemmi; Bangun, Andreas Xaverio (Fakultas Kedokteran, Kedokteran Gigi, dan Ilmu Kesehatan, 2025)
Hypertension is a leading global cause of mortality, with a high prevalence among the elderly. Dietary patterns constitute a modifiable risk factor. This study aimed to analyse the association between dietary patterns and the incidence of hypertension among the elderly. A quantitative study with a cross-sectional design was conducted at the Medan Johor Community Health Centre. A sample of 90 elderly individuals was selected via purposive sampling. Dietary data were collected using a Food Frequency Questionnaire (FFQ), and blood pressure was measured using a sphygmomanometer. Data analysis employed the Chi-Square test. A total of 72.2% of respondents had hypertension, and 65.6% had poor dietary patterns. Bivariate analysis indicated a significant association between dietary patterns and the incidence of hypertension (p-value = 0.022; OR = 0.268). Elderly individuals with poor dietary patterns had a 0.268 times higher risk of hypertension compared to those with good dietary patterns. A significant association exists between poor dietary patterns and the incidence of hypertension among the elderly at the Medan Johor Community Health Centre. Promotive and preventive efforts through balanced nutrition education are essential.